An Analysis of Illocutionary Speech Acts In Instagram Comments on @Skintificid Posts - Bella Yanti Marpaung; Fadya Sahira Zulham; Khairunnisa Fitri; Niaarota Buulolo; Rachel Mutiara Lolita Marpaung; Meisuri Meisuri (Komprehensif, 2026)
This study aims to analyze the various types of illocutionary speech acts present in comments on the Instagram account @skintificid, focusing on identifying which type is most frequently employed by users in reaction to promotional content. A qualitative descriptive method is utilized, aided by basic quantitative analysis to determine the occurrence and percentage of each illocutionary act. Data were gathered from five posts made on Instagram on March 10, 12, 14, 16, and 17, 2026, including 50 selected comments. The analysis follows Searle’s (1979) framework for categorizing illocutionary acts, which includes assertives, directives, commissives, expressives, and declaratives. The results indicate that all five categories of illocutionary acts are present, with assertive acts being the most prevalent at 44%, followed by commissives at 26% and expressives at 24%. In contrast, directives account for 4% and declaratives for 2%, appearing less often. These results imply that users on Instagram primarily engage in evaluative, emotional, and intention-driven communication when interacting with promotional content. Additionally, the illocutionary acts signify the interactions between customers and brands, with assertives serving as electronic word-of-mouth (e-WOM), expressives demonstrating emotional involvement, and commissives reflecting an intention to purchase. Overall, this research highlights the significant impact that comment sections on Instagram have in shaping brand image and influencing prospective consumers within the realm of digital marketing.